Evaluation of Codec Behavior in IP and ATM Networks - Naegele-Jackson, Susanne; Hilgers, Ursula; Holleczek, Peter (Informatica, 2001)
As multimedia applications are becoming more and more widespread, there is a need for video data to be transmitted over IP as well as ATM networks. While ATM with its Quality of Service features is able to provide adequate transmission guarantees for the strong timing and bandwidth constraints of video data, the transfer of video over IP networks is an issue wherever ATM is not available and applications are used that can tolerate longer delays and occassional impairments. The study evaluates a codec for teleconferencing and teleteaching applications over an IP network. A direct comparison is made to a MJPEG codec for similar applications over ATM with empirical measurements in a simple testbed. The main focus lies on the Quality of Service parameters delay, jitter and subjective picture quality. Network overload situations and realistic network behavior are simulated and their impact on picture quality is evaluated.
UnivIS-Import:2015-04-16:Pub.2001.zwiss.rrze.ksys.evalua
Keywords: ATM; IP; QoS; Video transmissions